A customizable cost-effective design for printed circuit board-based nanolayered gold screen-printed electrode: From fabrication to bioapplications - Ghorbanzadeh, Sadegh; Naghib, Seyed Morteza; Sadr, Ali; Molaabasi, Fatemeh; Zhang, Wei (Frontiers in Bioengineering and Biotechnology, 2022)
Screen-printed electrodes (SPEs) are promising candidates for fabricating biosensing platforms in the laboratory and industry due to their advantages. The primary method for fabricating SPEs is 2D printing, however the commercial SPEs have some limitations for researchers. Specific port and connection, inflexible design, high price, and decreased efficiency after a short time are counted as the weaknesses. Here, we introduce high performance, feasible, and cost-effective gold SPEs based on combination of printed circuit board substrate (PCBs) and sputtering method for electrochemical biosensing platforms. First, we discuss a general gold SPE development procedure that helps researchers to develop their own design. In the second step, the final developed version of SPEs was characterized, showing the positive performance in electrochemical parameters because of the optimization in design and fabrication steps. In the study's final phase, SPEs were used to fabricate a simple platform for breast cancer cell detection as a proof of concept without using any linker or labeling step. The designed immunosensor is very simple and cost-effective that showed a linear calibration curve in the range of 10 − 2× 102 cells mL−1 (R2 = 0.985, S/N = 3). This research can be used as a reference for future studies in SPEs-based biosensors because of the flexibility in design and the accessibility of required manufacturing equipment.